Submission of claim from 26th March 2018 t0 22nd April 2018 due to diaphragm wall - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of claim from 26th March 2018 t0 22nd April 2018 due to diaphragm wall of BRACU new campus development project.